2000
DOI: 10.1159/000006679
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Neuronal NO Synthase with Urotensins I and II in the Caudal Neurosecretory Neurons and the Urophysis of the Teleost <i>Oreochromis niloticus</i>

Abstract: The intracellular distribution of neuronal nitric oxide synthase (nNOS) was studied in the caudal neurosecretory system of a teleost, Oreochromis niloticus (Cichlids), by means of post-embedding immunogold labeling with a polyclonal antibody directed against nNOS of human origin. Ultrastructural examination demonstrated that neuronal NOS-like molecules are distributed within the Dahlgren cell perikarya, the neurosecretory axons, and the urophysial axon terminals. In the neurosecretory somata, gold particles fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Biochemical and Western blot analyses also indicated that a constitutive NOS is expressed in fish caudal spinal cord, which is similar to mammalian nNOS [Cioni et al, 1998]. In the caudal neurosecretory neurons and the urophysis, nNOS is colocalized with caudal neurohormones, urotensins I and II [Cioni and De Vito, 2000]. These findings have suggested that NO is implicated in the modulation of hormone release in teleosts in a similar way to mammals [Cioni et al, 2002].…”
Section: Introductionmentioning
confidence: 76%
“…Biochemical and Western blot analyses also indicated that a constitutive NOS is expressed in fish caudal spinal cord, which is similar to mammalian nNOS [Cioni et al, 1998]. In the caudal neurosecretory neurons and the urophysis, nNOS is colocalized with caudal neurohormones, urotensins I and II [Cioni and De Vito, 2000]. These findings have suggested that NO is implicated in the modulation of hormone release in teleosts in a similar way to mammals [Cioni et al, 2002].…”
Section: Introductionmentioning
confidence: 76%
“…Neuronal NOS-like enzymes were localized in neuroendocrine neurons of the preoptichypothalamo-hypophysial and caudal neurosecretory system by means of NADPHd histochemistry and NOS immunohistochemistry [7,13], and direct evidence of colocalization of nNOS with arginine-vasotocine (AVT) or urotensins in these neurons was provided by means of double immunolabeling methods [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…Since nos3 has not been identified in fishes, this evidence is probably due to the cross-reactivity of Nos1 with heterologous antibodies. The intracellular distribution of Nos1 molecules was analyzed for NOSI, NOSI/UI and NOSII/UII by single and double gold immunoelectron microscopy in order to compare the distribution of Nos1-like molecules with that of the urophysial peptides [197]. The subcellular localization of fish Nos1 correlates well with the biochemical data.…”
Section: Nitric Oxide In the Cnssmentioning
confidence: 99%